Superelastic CuAlBe wire-based sliding lead rubber bearings for seismic isolation of bridges in cold regions. (15th November 2021) - Zheng, Wenzhi; Wang, Hao; Hao, Hong; Bi, Kaiming
Highlights: A novel CuAlBe-SLRB is proposed for seismic protection of continuous bridges in cold regions. The numerical model of CuAlBe-SLRB is developed and verified using the experimental results of sliding-LRB and CuAlBe wire. A numerical searching method is suggested to achieve the optimal parameters of CuAlBe-SLRB. Effectiveness of CuAlBe-SLRB for response mitigation of bridges against low temperature is discussed and assessed. Abstract: To enhance the re-centering capability of sliding-lead rubber bearing (sliding-LRB) comprising the sliding device and LRB in series and overcome the degradation of the widely used Nitinol (NiTi) wires at low temperatures, a novel copper aluminum beryllium wire-based sliding lead rubber bearing (CuAlBe- SLRB) is proposed for seismic protection of bridges in cold regions. The re-centering performance is achieved by adding the superelastic CuAlBe wires into the sliding-LRB. The numerical model is developed and verified using the experimental results of the sliding-LRB and CuAlBe wire, respectively. A numerical searching method is suggested to design the optimal parameters of CuAlBe-SLRB system. Nonlinear dynamic analyses are conducted to investigate the seismic response of bridges with CuAlBe-SLRBs for varying isolation periods. The responses of the bridges with CuAlBe-SLRBs and sliding-LRBs are compared. Results reveal that the CuAlBe-SLRB system is more effective to enhance the bridge performance than the sliding-LRB system against earthquakes and dependable restorability can be achieved in cold regions.